Before (and beyond) Kant’s Paralogisms: Wolff’s Psychologia Rationalis (1734) and Mendelssohn’s Phaedon (1767) - Sales Vilalta, Guillem (Con-Textos Kantianos. International Journal of Philosophy, 2025)
This paper defends two theses concerning the relationship between Kant’s critique of Rational Psychology and the contributions to this discipline made by Christian Wolff and Moses Mendelssohn, namely: (I) that Wolff’s Psychologia Rationalis (1734) is not in fact vulnerable to Kant’s charges, not only because it seeks to explain empirical data, but more crucially because its most basic explanatory ground is itself derived from experience;  and that Mendelssohn’s Phaedon (1767), which Kant regarded as a prime example of Rational Psychology, likewise is not adequately captured by Kant’s critique. To do so, the paper will include: (1) an introduction outlining the topic and its interest;  a section on Wolff’s Rational Psychology; (3) an analysis of Mendelssohn’s modification of Wolffian Psychology; and some concluding remarks
Keywords: Christian Wolff; Moses Mendelssohn; Immanuel Kant; Psychologia Rationalis; Phaedon